Predicting heterogeneous ice nucleation with a data-driven approach - Martin Fitzner (Nature Portfolio, 2020)
Heterogenous ice nucleation is a ubiquitous phenomenon, but predicting the ice nucleation ability of a substrate is challenging. Here the authors develop a machine-learning data-driven approach to predict the ice nucleation ability of substrates, which is based on four descriptors related to physical properties of the interface.